2007
DOI: 10.1108/02610150710735471
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring minority graduate students: issues and strategies for institutions, faculty, and students

Abstract: Purpose -The purpose of this paper is to examine mentoring relationships involving minority graduate students in the USA. Design/methodology/approach -The authors take a multifaceted approach to providing strategies to improve the opportunities of minority students to acquire mentors by directing attention to institutional practices, faculty development, and the behaviors of students themselves. Findings -Mentoring relationships provide critical personal and professional development opportunities throughout on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
129
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 25 publications
(30 reference statements)
2
129
0
Order By: Relevance
“…In this context, mentoring provides academic student protégés with academic guidance, career development, personal guidance, and overall aid in the socialization of the graduate student (Thomas et al, 2007). As suggested by Kram (1985), cited in Humble (2006: 3) mentoring consists of two functions: career, preparing individuals for a career; and psychosocial, providing social support.…”
Section: Conceptualising Quality Supervisionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, mentoring provides academic student protégés with academic guidance, career development, personal guidance, and overall aid in the socialization of the graduate student (Thomas et al, 2007). As suggested by Kram (1985), cited in Humble (2006: 3) mentoring consists of two functions: career, preparing individuals for a career; and psychosocial, providing social support.…”
Section: Conceptualising Quality Supervisionmentioning
confidence: 99%
“…Jowett and Stead (1994: 25) argue that mentors need skills over and above their professional ones, especially about how to provide support to their students, thus making mentoring "a potentially valuable development vehicle in many contexts, not least within higher education." Thomas et al (2007) observed that most definitions on mentoring agree that mentoring goes beyond mere career development, but includes the building of a strong personal relationship between the mentor and the mentee, which has an instrumental and psychological function. For the mentor to perform a functional role he/ she must be knowledgeable, experienced, visible and powerful and since not all faculty members have these attributes it follows also that they can't all be credible mentors (Thomas et al (2007).…”
Section: Conceptualising Quality Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in a study involving university faculty, women reported being in more mentoring relationships than did men (Smith, Smith, & Markham, 2000). In contrast, another study of mentoring relationships in higher education found that women mentors experienced difficulties in mentoring male protégés especially for those protégés who lacked confidence in women mentors' competencies or credibility (Thomas, Willis, & Davis, 2007). These findings are similar to another study (Ragins & Cotton, 1993), where though women expressed as much willingness to mentor as men, they anticipated significant drawbacks in becoming a mentor.…”
Section: Gender and Mentoringsupporting
confidence: 67%
“…Protégés have been paired with mentors in many ways such as similarity in interests, backgrounds, and geographic proximity (Furano, Roaf, Styles, & Branch, 1993;Garcia, 1992). In order to find out why certain mentoring relationships are rich in the functions they provide and the outcomes they produce, and why certain individuals are naturally inclined to these relationships, mentoring researchers examined mentor-protégé dynamics through the lens of gender (Kram & Bragar, 1992;Noe, 1988b;Ragins, 1989Ragins, , 1999Ragins & Cotton, 1999;Ragins & Scandura, 1997), ethnicity (Ragins, 1997;Ragins & McFarlin, 1990;Thomas, Willis, & Davis, 2007), culture (Galbraith & Cohen, 1995;Johnson-Bailey & Cervero, 2002), and personality variables (Aryee, Lo, & Kang, 1999;Bono & Colbert, 2005;Judge & Kammeyer-Mueller, 2007;Kim & Kim, 2007;Turban & Dougherty, 1994).…”
Section: Mentoringmentioning
confidence: 99%